2020
DOI: 10.3389/fgene.2020.588670
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Inhibits Cell Viability and Migration, and Induces Cell Apoptosis by circ_0009112/miR-708-5p Axis Through PI3K/AKT Pathway in Osteosarcoma

Abstract: Osteosarcoma is a primary tumor of bone and its incidence is increasing. Schisandrin B (Sch B), a generally used lignan in Chinese medicine, has been found to repress cancer progression. This study aims to reveal the effects and regulatory mechanism of Sch B in the viability, apoptosis and migration of osteosarcoma cells. In this study, we found circ_0009112 expression was higher and miR-708-5p expression was lower in SaOS2 and U2OS cells than in hFOB1.19 cells. Circ_0009112 expression was downregulated, but m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…MiRNAs are short noncoding RNAs that bind to their 3 0 /5 0untranslated regions at the post-transcriptional level to regulate gene expression. 24 Studies have shown that miRNAs play an important role in gene expression by regulating post-transcriptional translation, which may be involved in the regulation of a variety of disease progression. 6 Without exception, studies have reported that miR-708-5p plays an important role in a variety of physiological and pathological processes.…”
Section: Discussionsupporting
confidence: 54%
“…MiRNAs are short noncoding RNAs that bind to their 3 0 /5 0untranslated regions at the post-transcriptional level to regulate gene expression. 24 Studies have shown that miRNAs play an important role in gene expression by regulating post-transcriptional translation, which may be involved in the regulation of a variety of disease progression. 6 Without exception, studies have reported that miR-708-5p plays an important role in a variety of physiological and pathological processes.…”
Section: Discussionsupporting
confidence: 54%
“…Such molecules sequester miRNAs in a complex regulatory network in which RNAs can regulate each other by competing for a limited pool of miRNAs [ 50 ]. In this regard, many long non-coding RNAs have been included in these ceRNA networks, including NONRATT009773.2/miR-708-5p/CXCL13 in bone cancer [ 51 ]; LINC00514/miR-708-5p/HOXB3 in cervical squamous cell carcinoma [ 52 ]; LINC00665/miR-708 and miR-142-5p/RAP1B in osteosarcoma [ 53 ]; Meg3/miR-708/SOCS3 in colorectal cancer [ 54 ]; LOXL1-AS1/miR-708-5p/USF1 and NF-κB [ 55 , 56 ]; and the RNAs circ_0009112 and MINCR, sponging miR-708-5p and regulating PI3K/AKT and Wnt/β-catenin pathways [ 57 , 58 ].…”
Section: Mir-708 Overviewmentioning
confidence: 99%
“…8 So far, there are a number of studies published exploring the effect of polyphenols on colorectal cell lines or animal models. 9−11 Schisandrin B (Sch B), a lignan extracted from the fruit of Schisandra chinensis, has been reported for its anticancer properties in various cancers, for example, liver cancer, 12 breast cancer, 13,14 ovarian cancer, 15 glioma, 16 osteosarcoma, 17 and gastric cancer. 18,19 More recently, studies have shown that Sch B was able to prevent or treat colitis-associated colon cancer.…”
mentioning
confidence: 99%
“…Schisandrin B (Sch B), a lignan extracted from the fruit of Schisandra chinensis, has been reported for its anticancer properties in various cancers, for example, liver cancer, breast cancer, , ovarian cancer, glioma, osteosarcoma, and gastric cancer. , More recently, studies have shown that Sch B was able to prevent or treat colitis-associated colon cancer. , Although the antitumor activities of Sch B have been confirmed in various cancer types, the potential mechanism of Sch B seems much more complex, ranging from cell cycle arrest to programmed cell death. For example, in liver cancer, Sch B induced G0/G1 cell cycle arrest and apoptosis by upregulating caspase-3 and Bcl-2 family members in cholangiocarcinoma (CCA), and reduced tumor growth in a xenograft mouse model .…”
mentioning
confidence: 99%
See 1 more Smart Citation